Loopholes and the Incidence of Public Services: Evidence from Funding Career & Technical Education - Thomas Goldring; Brian A. Jacob; Daniel Kreisman; Michael D. Ricks (Institute of Labor Economics (IZA), 2024)
In 2015, Michigan increased it Career and Technical Education (CTE) funding and changed its funding formula to reimburse programsbased student progression through program curricula. Although this change nearly doubled program completion rates, student enrollment and persistence were unaffected; instead, administrators accelerated student progress by reorganizing course curricula around notches in the new funding formula. As a result of response heterogeneity, 30% of the funding increase is transferred away from high-poverty districts to more affluent ones, underscoring how supply-side responses to loopholes shape the incidence of public services.
Keywords: I21; J24; I24; 330; career and technical education; school funding; loopholes